The Development of Network of Case Manager Nurse for Patients with ST Elevation Myocardial Infarction in Sakon Nakhon Province - chantamee, Wachira; Daekhunthod , Tasanee; Sridama, Uraiwan; chaiyara, Saithip (Medical Journal of Sakon Nakhon Hospital, 2024)
This research and development aimed to develop a network of case manager nurses taking care of patients with acute myocardial infarction, and to study outcomes after development. The sample groups were selected by purposive sampling according to the specified qualifications from Sakon Nakhon hospital and 18 network hospitals consisted of 1) network development group, 37 nursing executives and advanced practice nurses, 2) 20 registered nurse assigned for caring patients with acute myocardial infarction and 3) 200 patients with acute myocardial infarction divided into experimental groups (100 patients received nursing care using the nurse case manager model) and control group (100 patients received standard nursing care). The research was performed in 6 steps from August 2023 to May 2024. The research tools included the practice assessment form for developing care model for patients with acute myocardial infarction, developing the competencies of case manager nurses and network supervision. Data collection tools included focus groups, data collection form, competency assessment form, clinical supervision plan, and satisfaction assessment form. Data were analyzed by using the frequency, percentage, mean, standard deviation, independent t-test, and paired t-test. The results of the study found that 1) the Sakon Nakhon province’s network of nurse case manager for taking care of patients with acute myocardial infarction consisted of 3 components including the nurse case manager competency, case manager nurse model and network clinical supervision, resulting in the same guideline following and 2) after model development, most patients received standard treatment, got access to services in a timely manner and received angioplasty. The incidence of patient adverse event statistically significant decreased compared to that before model development (p < 0.05).